Formulasi dan Analisis Harga Pokok Bibit serta Harga Maksimum Bibit dan Pakan pada Usaha Ternak Ayam Ras Petelur - Yusmichad Yusdja; Aladin Nasution (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1993)
The main objective of this study is to analyze the unit cost of day old chicks of layer and the break event point of small eggs farm. The data was taken from the survey conducted in 1990 and 1993 in West Java. The data was collected through indepth study in the poultry breeding farms and the egg production farms. The result showed that the unit cost of day old chicks is Rp 617 per chick where as the actual price is much higher i.e. p 1350 per chicks. This information showed that the small farmer have paid high marketing cost. The research has also shown that the break even level of eggs farm is mainly depend on feeding price and egg price. The ratio of egg price to feed price at the break event point 2,57.